CNT induced β-phase in polylactide: Unique crystallization, biodegradation, and biocompatibility - Singh N.K.; Singh S.K.; Dash D.; Gonugunta P.; Misra M.; Maiti P. (My University, 2025)
The effect of multi-walled carbon nanotube (MWCNT) on the crystal structure, unique crystallization, mechanical behavior, enzymatic degradation, and significant improvement in biocompatibility of polylactide (PLA) nanohybrid has been reported. Functionalization of carbon nanotube using stearyl alcohol has been carried out and has been confirmed through FTIR and Raman spectroscopy. PLA nanohybrids have been synthesized using functionalized and neat MWCNT through solution route, and the improved level of dispersion of MWCNT has been achieved in PLA matrix. High-magnification transmission electron microscope images indicate the unique adsorption of PLA chain leading to the crystallization of β-phase structure on the surface of the functionalized MWCNT against the usual crystallized α-form of pure PLA. The presence of β phase in nanohybrids has been confirmed through electron diffraction pattern, differential scanning calorimetry thermograms, and X-ray diffraction patterns. The improved and diverse mechanical, thermal properties, and crystallization kinetics have been explored with the special emphasis on the relaxation behavior of β phase in dynamic mechanical analysis. The cause of these developments has been appraised from the interaction point of view as calculated from the interaction parameter (χ) using melting-point depression technique. The rate of biodegradation has been studied in detail with plausible mechanism in Proteinase K enzyme media showing their specificity and tuning of biodegradation rate followed by their optimization. For biomedical applications, the effect of pure polymer and nanohybrids on circulating blood cells has been evaluated in detail, and the hemocompatible nature of the nanohybrids has been revealed, suppressing the cellular toxicity of MWCNT. © 2013 American Chemical Society.